Essential Check Point FireWall-1 NG : an installation, configuration, and troubleshooting guide - Welch-Abernathy, Dameon D. (Addison-Wesley, 2004)
"When it comes to security products and technologies, experience is far and away the best teacher. PhoneBoy has been installing, running, and supporting Check Point FireWall-1 for years, and his experience shows in this book. Save yourself the pain of learning from your own mistakes--let PhoneBoy show you the right way to manage your FireWall-1 NG infrastructure." --Tina Bird, Computer Security Officer, Stanford University "Dameon has taken his original definitive guide and updated it thoroughly for NG. No other book is informed by his depth of experience with Check Point. Accept no substitutes!" --Matthew Gast, author of 802.11 Wireless Networks: The Definitive Guide "PhoneBoy is the de facto expert on this product, and people have been clamoring for an NG book from him since he published the first one. No one can compete with him." --Valerie M. Leveille, Professional Educator "Dameon is the foremost authority on FireWall-1. He has the knowledge to give details of FireWall-1 functionality that no other reference on this topic can." --Paul Keser, Senior Network Security Engineer, Raytheon ITSS/NASA Ames Research Center "This book is the Swiss army knife solution for Check Point FireWall-1 NG." --Thomas Warfield, TNT-OK.com Now there's a definitive insider's guide to planning, installing, configuring, and maintaining the newest version of the world's #1 firewall: Check Point FireWall-1 ® Next Generation. Leading Check Point support authority Dameon Welch-Abernathy (a.k.a. PhoneBoy) offers exclusive hands-on tips, techniques, checklists, and detailed sample configurations you can use right now to improve reliability, efficiency, and manageability in your Check Point environment. The author's previous Check Point FireWall-1 guide became an instant bestseller, earning the praise of security professionals worldwide. This new book has been thoroughly revamped to reflect Check Point FireWall-1 NG's powerful new features, and it includes even more expert solutions from PhoneBoy's FireWall-1 FAQ, the Web's #1 independent Check Point support site. Whether you're a security/network architect, administrator, or manager, you'll find it indispensable. Whether you're running FireWall-1 NG on UNIX or Windows platforms, this book brings together expert guidance for virtually every challenge you'll face: building your rulebase, logging and alerting, remote management, user authentication, inbound/outbound content restriction, managing NAT environments.